2012
DOI: 10.1364/ao.52.000b20
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of optical and structural properties of ceramic boron nitride by terahertz time-domain spectroscopy

Abstract: Six types of hexagonal boron nitride are investigated by terahertz time-domain spectroscopy. The loss coefficient is shown to be linear with porosity, while variations in refractive index indicate the distribution of porosity within the structure. Pyrolytic boron nitride is demonstrated to be suitable as a terahertz optical material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 17 publications
3
9
0
Order By: Relevance
“…8b), which showed very low absorption behavior of BN in the range 0.2-3.0 THz, for example, at 2.0 THz the mean value is 56 AE 12 cm. 24 With respect to these results, the absorption coefficient revealed similar slowly growing tendency in the investigated THz region. 24 With respect to these results, the absorption coefficient revealed similar slowly growing tendency in the investigated THz region.…”
Section: Dielectric Properties Of Pbn In Thz Regionsupporting
confidence: 64%
See 2 more Smart Citations
“…8b), which showed very low absorption behavior of BN in the range 0.2-3.0 THz, for example, at 2.0 THz the mean value is 56 AE 12 cm. 24 With respect to these results, the absorption coefficient revealed similar slowly growing tendency in the investigated THz region. 24 With respect to these results, the absorption coefficient revealed similar slowly growing tendency in the investigated THz region.…”
Section: Dielectric Properties Of Pbn In Thz Regionsupporting
confidence: 64%
“…The variation of the refractive indices found by these authors is in the same range as was found in our study, however, the variations were attributed also to the changes in the porosity of the investigated samples. Distinct detection of the differences in refractive indexes related to the birefringence of pBN 23,24 reported in the literature could be responsible for these variations. Distinct detection of the differences in refractive indexes related to the birefringence of pBN 23,24 reported in the literature could be responsible for these variations.…”
Section: Dielectric Properties Of Pbn In Thz Regionmentioning
confidence: 94%
See 1 more Smart Citation
“…Using Equation(2) and Equations(3), refractive indices and attenuation coefficients of the counterfeit ICs ofFigure 3are calculated as 1.82 and 2.475×10 4 dB/cm respectively. The calculated refractive indices are in the reported range of refractive indices for ceramics16 . This confirms the validity of the experiment.b) THz techniques in reflection modeThe different layers of a given component are extracted by using reflection mode THz measurement.…”
mentioning
confidence: 71%
“…Variations of refractive indices of materials in different THz frequencies can give a signature to characterize them 16,17 . In Figure 7 refractive indices of two authentic ICs and their counterfeit one are depicted.…”
Section: C) Broadband Terahertz Characterization Of the Refractive Indexmentioning
confidence: 99%